The Basilica of Saint John Lateran to 1600 - Bosman, Lex 1956-; Haynes, Ian 1967-; Liverani, Paolo 1959- (British School at Rome studies, 2020)
The Archbasilica of St John Lateran is the world's earliest cathedral. A Constantinian foundation pre-dating St Peter's in the Vatican, it remains the seat of the Bishop of Rome, the Pope, to this day. This volume brings together scholars of topography, archaeology, architecture, art history, geophysical survey and liturgy to illuminate this profoundly important building. It takes the story of the site from the early imperial period, when it was occupied by elite housing, through its use as a barracks for the emperor's horse guards to Constantine's revolutionary project and its development over 1300 years. Richly illustrated throughout, this innovative volume includes both broad historical analysis and accessible explanations of the cutting-edge technological approaches to the site that allow us to visualise its original appearance